trig

posted by .

Which expression is equivalent to cos(4x) + cos(2x)?

  • trig -

    cos(4x) + cos(2x)
    =cos(3x+x)+cos(3x-x)
    =2cos(3x)cos(x)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. trig

    Reduce the following to the sine or cosine of one angle: (i) sin145*cos75 - cos145*sin75 (ii) cos35*cos15 - sin35*sin15 Use the formulae: sin(a+b)= sin(a) cos(b) + cos(a)sin(b) and cos(a+b)= cos(a)cos(b) - sin(a)sin)(b) (1)The quantity …
  2. pre-cal

    Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos 6x can be expressed as a series of terms that involve sin x or cos x only, but the end result is not a simplification. sin 2x = 2 sinx cosx cos 6x = 32 cos^6 x -48
  3. Math - Solving Trig Equations

    What am I doing wrong? Equation: sin2x = 2cos2x Answers: 90 and 270 .... My Work: 2sin(x)cos(x) = 2cos(2x) sin(x) cos(x) = cos(2x) sin(x) cos(x) = 2cos^2(x) - 1 cos(x) (+/-)\sqrt{1 - cos^2(x)} = 2cos^2(x) - 1 cos^2(x)(1 - cos^2(x))
  4. Trig

    Which expression equivalent to: cos(theta + pi/2). A)cos theta B)-cos theta C)sin theta D)-sin theta my book doesnt give examples of this but my crack at it would be C b/c distributive property?
  5. TRIG!

    Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1 - (3/4)sin^2 2x work on one side only! Responses Trig please help! - Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 …
  6. trig

    The expression 4 sin x cos x is equivalent to which of the following?
  7. Trigonometry

    Write equivalent equations in the form of inverse functions for a.)x=y+cos è b.)cosy=x^2 (can you show how you would solve) a.) x= y+ cos è cos è = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2)
  8. Calculus (help Steve plz)

    1) if w = <-8, 15>, find ||w||? 2) which expression is equivalent to (sin x+1) (sin x -1)?
  9. trig

    choose the expression that is equivalent to the given expression. 2 cos^2 4x-1
  10. pre-calculus

    which expression is equivalent to (sinx+1)(sinx-1)?

More Similar Questions